Membangun Ekosistem Sekolah Masa Depan dengan Pendekatan Kolaboratif Inklusif - Khairul Anam; Rugaiyah Rugaiyah; Madhakomala Madhakomala (Neolectura, 2022)
Inclusive collaboration referred to in this study is a planned and joint effort between education stakeholders to create a safe, comfortable and productive atmosphere in the student learning process. Along the way, the problem that most often arises is bullying. Regarding these problems, the purpose of this research is to examine in the literature how to build the school ecosystem of the future. To get the data of this research, the writer conducted a library approach. The data collected leads to discussions about educational issues, the influence faktors of inclusive collaboration, and how to build an inclusive partnership between schools and students, schools with parents, and schools with the environment.